Long-term learning and forgetting of feature binding in verbal free recall. Issue 6 (June 2023) - Sacripante, Riccardo; Della Sala, Sergio; Logie, Robert H
Temporary feature bindings can be learned under specific experimental conditions. However, how this learning occurs and how it is forgotten over long intervals is unclear. We addressed this question with repeated presentation of an array of coloured shapes followed by verbal free recall after delays of 1 day, 1 week, and 1 month. A total of 120 participants viewed 24 repetitions of the same study array of six objects each with two features (shape and colour). After 24 trials, 61 participants reported becoming aware of the repetition while 59 reported being unaware. Memory performance improved across trials, with aware participants showing faster learning than unaware participants whose performance appeared to reflect the capacity of short-term visual memory across all repetitions. Both aware and unaware participants recalled some of the array after their allocated delay, showing that learning had occurred during repetition trials, even for unaware participants who showed little or no improvement across 24 repetition trials. Memory for binding showed no change after 1 day compared with performance on the 24th repetition trial, was significantly lower for participants tested after 1 week, and was lower still for those tested after 1 month. Findings are interpreted as consistent with both a short-term, limited capacity visual cache that supports performance during early repetition trials, before learning can have occurred, and gradual strengthening across trials of an episodic long-term memory trace that supports learning. If the episodic trace exceeds the threshold of awareness, this accelerates learning.